Analisis Pengaruh Faktor-Faktor Minat Beli Ulang dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Pelanggan Hestâ€™in Modiste di Jakarta) - Pastikarani, Dyah Adhisti; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2016)
This research was motivated by declining sales in Hest'in Modiste. This is due to the increased level of customers dissatisfaction Hest'in Modiste. Seeing this, the research was conducted to determine how much influence service quality, product quality, and customer relationship marketing with customer satisfaction as an intervening variable on repurchase intention in Hest'in Modiste. In this study, using three independent variables with one intervening variables and dependent variable.The population are customers Hest'in Modiste. This research uase as a sample of 100 respondents by the criteria have been using the services of Hest'in Modiste more than twice. Then the data were analyzed using multiple regression analysis channeled through the SPSS program.Based on the research results, the result that service quality, product quality, and customer relationship marketing positive effect on customer satisfaction with the regression coefficient is Y1 = 0,326X1 + 0,361X2 + 0,322X3 andÂ  customer satisfaction has positive effect on the repurchase intention with the regression coefficient is Y2 = 0.494 Y1.